2015
DOI: 10.1055/s-0035-1546207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Processing on the Content of Toxic Carboxyatractyloside and Atractyloside and the Microbiological Status of Xanthium sibiricum Fruits (Cangʼerzi)

Abstract: The dried ripe fruits of Xanthium sibiricum (Cang'erzi) are used in traditional Chinese medicine for the treatment of nasal congestion, nasal discharge, allergic rhinitis, sinusitis, and wind-cold headaches. Carboxyatractyloside and atractyloside are important constituents of the fruits because these diterpenoid glycosides are responsible for their toxicity. In order to evaluate procedures for reducing the amount of the more toxic carboxyatractyloside, the fruits were dried and heated with different methods. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…This can be explained because the content of CAR in the RXF extract is the highest. In other studies, it was shown that the in vivo toxicity of CAR is 10 times higher than that of ATR [38], which may be due to the carboxylic group in position C-4 ′ of CAR that seems to be responsible for its higher toxicity [16]. As this study showed, the t 1/2 values of CAR in the PXF group were a little shorter than those in the RXF group.…”
Section: Pharmacokinetic Studysupporting
confidence: 45%
See 1 more Smart Citation
“…This can be explained because the content of CAR in the RXF extract is the highest. In other studies, it was shown that the in vivo toxicity of CAR is 10 times higher than that of ATR [38], which may be due to the carboxylic group in position C-4 ′ of CAR that seems to be responsible for its higher toxicity [16]. As this study showed, the t 1/2 values of CAR in the PXF group were a little shorter than those in the RXF group.…”
Section: Pharmacokinetic Studysupporting
confidence: 45%
“…IS solutions of chloramphenicol were prepared in methanol to produce a final concentration of 100 ng/mL. QC samples were prepared at concentrations of 11.02, 275.50, and 551 ng/mL for 3,4-dihydroxybenzoic, 10.05, 502.50, and 1005 ng/mL for 5-CQA, 12.75, 1275, and 2550.00 ng/mL for 3-CQA, 28.2, 282, and 2820 ng/mL for CA, 15.50, 1550, and 2500 ng/mL for 4-CQA, 16.50.4, 825, and 1650 ng/mL for 1,3-diCQA, 10.13, 262.50, and 525 ng/mL for FA, 13.13, 262.50, and 525 ng/mL for 3,5-diCQA, 10.50, 210, and 420 ng/mL for 1,5-diCQA, 15.50, 310, and 620 ng/mL for 3,4-diCQA, 13.50, 675, and 1450 ng/mL for CAR, 15.25, 305, and 610 ng/mL for 4,5-diCQA, and 10.50, 1575, and 3150 ng/mL for ATR. All solutions were stored in the refrigerator at 4 • C until use.…”
Section: Stock Solutionsmentioning
confidence: 96%
“…Sesquiterpene lactones are the major chemicals in XF [6]. Atractyloside (ATR) and carboxyatractyloside (CATR) are believed to be the main injurious ingredients of this herb [10][11][12], which also exist in several Asteraceae plants such as Callilepsis laureola and Atractylis gummifera. The pharmacological and toxicological effects of ATR and CATR have been documented for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…with functions of scattering heat and awaking through the nose (Ruan & Li, 2007;Su et al, 2016). It is an important herbal medicine for the treatment of "Biyuan" in ancient clinical records, and allergic rhinitis and other nasal disease in modern usage (Han et al, 2006;Liu, Su, Zeng, Li, & Wu, 2012;Nikles et al, 2015).…”
Section: Introductionmentioning
confidence: 99%